2011
DOI: 10.1007/s00421-011-1878-3
|View full text |Cite
|
Sign up to set email alerts
|

Does a bout of strength training affect 2,000 m rowing ergometer performance and rowing-specific maximal power 24 h later?

Abstract: Rowers regularly undertake rowing training within 24 h of performing bouts of strength training; however, the effect of this practice has not been investigated. This study evaluated the impact of a bout of high-intensity strength training on 2,000 m rowing ergometer performance and rowing-specific maximal power. Eight highly trained male club rowers performed baseline measures of five separate, static squat jumps (SSJ) and countermovement jumps (CMJ), maximal rowing ergometer power strokes (PS) and a single 2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 56 publications
0
23
0
2
Order By: Relevance
“…Previous authors have recorded comparable decrements in jump performance, when participants have followed similar resistance protocols, at 24 h post-exercise [27,28]. However, ingestion of BCAA was shown to significantly attenuate these performance decrements, with 6 g BCAA resulting in ~2% increase and 18 g BCAA resulting in ~4% increase across both CMJ and SJ when compared to the placebo trials.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Previous authors have recorded comparable decrements in jump performance, when participants have followed similar resistance protocols, at 24 h post-exercise [27,28]. However, ingestion of BCAA was shown to significantly attenuate these performance decrements, with 6 g BCAA resulting in ~2% increase and 18 g BCAA resulting in ~4% increase across both CMJ and SJ when compared to the placebo trials.…”
Section: Discussionmentioning
confidence: 83%
“…However, this could be attributed to the more 'representative' nature of the ST in this study, as opposed to protocol completed by Howatson et al, [2]. The ST was designed to replicate the demands of traditionally practiced athletic strength sessions, rather than predominantly focus on inducing extreme levels of EIMD and subsequent decrements in functional performance and elevations in markers of muscle damage [16,27]. Repetitive high force, eccentric muscle actions, as used by Howatson et al, [2], result in amplified EIMD, as witnessed by the vast decrements in maximal voluntary contraction (~20-27%) [5,26] and increments in RMS across groups [2,29].…”
Section: Discussionmentioning
confidence: 98%
“…4,5 However, participants in these studies had considerably slower 2000-m performance times (6:51-6:56 and 6:58 min:s) than reported from club-standard rowers of a similar body mass taking part in research studies (6:33.7-6:38.6 min:s). [8][9][10] The rowing experience and performance level of the rowers used in the studies by Schabort et al 4 and Soper and Hume 5 might not be representative of well-trained senior club rowers. Therefore, the reproducibility of 2000-m ergometer performance in rowers of a higher standard is not yet known.…”
mentioning
confidence: 99%
“…For athletes who concurrently train for both strength and endurance, three weekly strength training sessions have been recommended (Garcia-Pallares and Izquierdo, 2011). Accordingly, rowers tend to perform two to three strength training sessions a week with the final session often occurring 24- to 48 h before a high-quality rowing session or even a competition (Gee et al, 2011a). However, it has been shown that high volume strength training can lead to the development of ‘residual fatigue’ and sub-optimal adaptations in rowing performance, compared to lower volume strength training (Izquierdo-Gabarren et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Previously many authors have investigated the effect of acute singular bouts of strength and power training on muscle function within cohorts of competitive athletes (Gee et al, 2011a; Gee et al, 2012; Raastad and Hallén, 2000). These authors have recorded decreases in various aspects of muscle function including peak power, jump height, sprint time, dynamic strength and symptoms of transient muscle damage following acute strength and plyometric training.…”
Section: Introductionmentioning
confidence: 99%